The Renminbi Rises Myths, Hypes and Realities of RMB Internationalisation and Reforms in the Post-Crisis World - Lo, C. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This book breaks new ground in research on the RMB's offshore market by addressing the myths, hypes and realities surrounding the rise of the Chinese Yuan. It is the first book to address the rise of the Renminbi by focusing on the structural factors behind it and drawing on the global, regional and domestic developments affecting its development.